Nursing Workforce Planning Approaches in Hospital - Meltem Demirgöz Bal (Association of Nurse Managers, 2015)
The quality of service supplied by nurses and the efficiency of hospitals are directly affected by the effective usage of employee planning in nursing. The insufficient number of nurses and low level quality of service given by nurses are very important problems in the world as well as in Turkey. In addition the improper distribution of nurses makes the problem much worse. The method of ratio of nurse/patient is being used traditionally for employee planning in nursing. The current method is based on patient classification systems that the patient care needs are taken into consideration. The right number of appropriately qualified nurses in clinics can improve the patient and hospital outcomes, while reducing nurse workloads and can increase the job satisfaction. The purpose of this paper is to emphasize the importance of ensuring the correct employment for the nurses working in inpatient institutions.